Biomimetic and Biohybrid Systems Second International Conference, Living Machines 2013, London, UK, July 29 August 2, 2013. Proceedings - Lepora, Nathan F.; Mura, Anna.; Krapp, Holger G.; Verschure, Paul F. M. J.; Prescott, Tony J. (Lecture Notes in Computer Science,, 2013)
This book constitutes the refereed proceedings of the second International Conference on Biomimetic and Biohybrid Systems, Living Machines 2013, held in London, UK, in July/August 2013. The 65 revised full papers presented were carefully reviewed and selected from various submissions. The papers are targeted at the intersection of research on novel live-like technologies inspired by scientific investigation of biological systems, biomimetics, and research that seeks to interface biological and artificial systems to create biohybrid systems